Seam quality: Experimental and modelling works using the structural equation methodology / Suzaini Abdul Ghani and Hugh Gong - Abdul Ghani, Suzaini; Hugh, Gong (Research Management Institute (RMI), 2010)
Seam quality in terms of appearance and strength were investigated for very light weight fabrics (weight less than 80 g m"). Seams were constructed with different sewing parameters, which included types of thread, stitch densities and needle size. Before constructing the seam for appearance and strength evaluation the mechanical properties of all fabrics were determined. The mechanical properties of 48 fabrics were determined using the Kawabata Evaluation System (KES-F), the Fabric Assurance Simple Test (FAST) and an Instron Tensile Tester. Evaluation of seam quality was performed with respect to all the sewing parameters and the seams were ranked accordingly. The same evaluation ranking for seam appearance and strength was used for further analysis using Structural Equation Modelling (SEM) under AMOS. SEM was used to establish the relationship between seam quality with respect to appearance and strength, and fabric mechanical properties. SEM was adopted to perform confirmative analysis to identify the fabrics mechanical properties that influence seam quality. From the experimental work, it was established that seams constructed with 100 % spun polyester thread with a ticket number of75gave the best ranking in terms of seam strength. This thread performed at optimum values when used with 6.5 stitches per centimetre (spcm) with a Metric needle size (Nm) of 90. For seam appearance, 100 % spun polyester with a ticket number of120 and Metric needle size of80 gave the best ranking. SEMestablished that extensibility andshear were the main fabric mechanical properties that determine seam quality ofvery light weight fabrics.